Sorption of Nitrate Salts from Wastewater without and with Modification Orange Peel - Abdulrazak N., Zainab (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
This investigation deals with the use of orange peel (OP) waste as adsorbent for removal of nitrate (NO3) from simulated wastewater. Orange peel prepared in two conditions dried at 60C° (OPD) and burning at 500 °C (OPB). The effect of pH: 2-10, contact time: 30- 180 min, sorbent weight: 0.5- 3.0 g were considered. The optimal pH value for NO3 adsorption was found to be 2.0 for both adsorbents. The equilibrium data were analyzed using Langmuir and  Freundlich isotherm models. Freundlich model was found to fit the equilibrium data very well with high-correlation coefficient (R2). The adsorption kinetics was found to follow pseudo-second-order rate kinetic model, with a good correlation (R2 > 0.95 and 0.94) for the orange peel adsorbent at 500 °C (OPB) and at 60 °C (OPD), respectively. The results showed that the orange  peel was found to be an attractive low cost adsorbent for the treatment of wastewater.